Cuando la comunidad «dice» el derecho: las asambleas de justicia indígena en Oaxaca - Vázquez Hernández, Irán (2024)
Assemblies represent an essential element in the indigenous justice of the communities in Oaxaca. In these types of gatherings, the community becomes a collective judicial body in order to address a violation of its normative system. What is their nature? How do they function? What notable elements do they incorporate in their development? This study aims to provide an approach to these questions through the tools of discourse analysis and studies on orality. To achieve its goal, it is divided into four sections: the first analyzes the typology, nature and status of indigenous justice assemblies; while the following sections focus on examining their procedural, discursive and oral dynamics.